2014
DOI: 10.1109/jstars.2013.2265751
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Solar Irradiance Spectra on Calculation of Narrow Band Top-of-Atmosphere Reflectance

Abstract: Extraterrestrial solar irradiance spectra detail the solar energy distribution over wavelengths, and numerous solar irradiance models are available within the remote sensing community. However, reference spectra may differ widely owing to differences in solar activity, measurement instruments and calibration. Six widely referenced solar spectra were selected in this work to examine their differences and the impacts of these differences on calculations of narrow band top-of-atmosphere reflectance using MERIS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Despite the observed low variability (other than Sun-Earth distance) of the spectral solar constant in spectral regions used for recent Earth observation (roughly 400-2600 nm), it has been observed that there are considerable differences between the commonly available estimates. For example, Zhang et al [8] studied the effects of using selections of spectral solar constant from six older models and found significant differences in the calculation of indices. They suggested the Thuillier model [4] seemed to be most accurate but found it hard to evaluate what establishes a "best" model.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the observed low variability (other than Sun-Earth distance) of the spectral solar constant in spectral regions used for recent Earth observation (roughly 400-2600 nm), it has been observed that there are considerable differences between the commonly available estimates. For example, Zhang et al [8] studied the effects of using selections of spectral solar constant from six older models and found significant differences in the calculation of indices. They suggested the Thuillier model [4] seemed to be most accurate but found it hard to evaluate what establishes a "best" model.…”
Section: Introductionmentioning
confidence: 99%
“…As noted in the introduction, previous studies [17,[20][21][22] have reported noticeable differences between these solar spectra that can be larger than their reported uncertainties. The state-of-the-art TSIS-1 SIM observations (Section 2.1.7) have order-of-magnitude reductions in uncertainty (<0.3% over the majority of the spectrum) relative to predecessor instruments, justifying our use of the TSIS-1 SIM as the baseline for comparing the other solar spectra against.…”
Section: Tsis-1 Hsrsmentioning
confidence: 77%
“…The VIIRS instrument on board the Suomi-National Polar-orbiting Partnership (SNPP) spacecraft, however, utilizes the Kurucz spectra [17,18] from MODTRAN 4.0 [16,19]. Previous studies [16,[20][21][22] have reported noticeable differences between these solar spectra that can potentially lead to incompatible retrievals from these satellite datasets.…”
Section: Introductionmentioning
confidence: 99%
“…The solar spectral irradiance measured at the ground increases from wavelengths of 350 to 500 nm to a maximum value of approximately 2250 Wm −2 μm −1 near 460 nm and then decreases above 500 nm to approximately 40 Wm −2 μm −1 at a 2400-nm wavelength. 9 The direct clear-sky irradiance regarding the altitude is expressed as follows: 10 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 1 ; 1 1 6 ; 2 8 5…”
Section: Solar Spectral Irradiancementioning
confidence: 99%